CRITICAL ANALYSIS OF PAK-CHINA RELATIONS IN THE PERSPECTIVE OF CPEC AND ITS IMPLICATION FOR SOUTH ASIA - Asad Ali; Khan Nawab; Zahra Ejaz (International Journal of Contemporary Issues in Social Sciences, 2024)
The Pakistan-China relationship has significantly evolved with the advent of the China-Pakistan Economic Corridor (CPEC). This transformative project, a cornerstone of China’s Belt and Road Initiative (BRI), has deepened economic and strategic ties between the two nations. CPEC, comprising extensive infrastructure, energy, and trade connectivity projects, aims to bolster Pakistan’s economic development while providing China with critical access to the Arabian Sea. However, the implications of this partnership extend beyond bilateral relations, impacting the geopolitical and economic landscape of South Asia. This analysis critically examines the developments and dynamics of Pak-China relations in the context of CPEC, highlighting the benefits and challenges, and assessing the broader regional consequences, including the responses from India and other South Asian countries. The study provides a nuanced understanding of the strategic imperatives driving CPEC and its potential to reshape regional alignments, economic dependencies, and security paradigms.